Perovskite precursor solution, perovskite light-absorbing layer and solar cell

CN122995505APending Publication Date: 2026-10-27TRINA SOLAR CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611470728.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-21
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

而目前制备的商业化尺寸的硅/钙钛矿叠层太阳能电池的光电转换效率仅为31.1%左右,其转换效率的下降,主要存在两个方面的原因:一是在叠层太阳能电池制备过程中,制备面积变大,钙钛矿成核不均匀,致使转换性能下降;二是大面积的叠层太阳能电池是在正常环境中制备,正常环境中的水氧会影响钙钛矿结晶过程,导致转换性能下降

Benefits of technology

[0041]本发明对喹唑啉-4-胺及其衍生物分子结构进行优化设计,使得设计分子能够在结晶过程中与钙钛矿中的二价阳离子(如Pb2+)形成强配位,对钙钛矿结晶控制起到帮助作用,并且设计分子的官能团还能够有效钝化钙钛矿成膜过程中形成的缺陷,使得钙钛矿质量得到明显提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122995505A_ABST
    Figure CN122995505A_ABST
Patent Text Reader

Abstract

The present application belongs to the field of perovskite solar cells, and particularly relates to a perovskite precursor solution, a perovskite light-absorbing layer and a solar cell. The perovskite precursor solution and the perovskite light-absorbing layer of the present application comprise a compound of Formula I, wherein the substituents R1, R2, R3, R4 and R5 are as described herein. The present application dopes the compound of Formula I in the perovskite layer, which can form strong coordination with the divalent cations (such as Pb 2+ ) in the perovskite during the perovskite crystallization process, helping to control the crystallization, and the functional groups thereof can effectively passivate the defects formed during the film formation process, so that the quality of the perovskite is significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of perovskite solar cells, specifically relating to perovskite precursor solutions, perovskite light-absorbing layers, and solar cells. Background Technology

[0002] Organic-inorganic metal halide perovskite materials have become the preferred material for the light-absorbing layer of solar cells due to their excellent photoelectric properties and low cost. Furthermore, the band gap of perovskite materials is tunable, allowing them to be stacked with other photovoltaic materials with different band gaps to form tandem solar cells, achieving extremely high photoelectric conversion efficiency. Currently, the photoelectric conversion efficiency of silicon / perovskite tandem solar cells has reached 34.6% with an area of ​​1 cm². 2 Currently, the photoelectric conversion efficiency of commercially available silicon / perovskite tandem solar cells is only around 31.1%. The decline in conversion efficiency is mainly due to two reasons: First, during the fabrication process of tandem solar cells, the fabrication area increases, and the perovskite nucleation becomes uneven, leading to a decrease in conversion performance. Second, large-area tandem solar cells are fabricated in a normal environment, where water and oxygen can affect the perovskite crystallization process, resulting in a decrease in conversion performance.

[0003] Additive engineering is an effective method to improve the crystallinity quality of perovskite thin films. However, current additives can only improve deep-level defects inside perovskite crystals and cannot be used to improve surface defects. Furthermore, commonly used additives can only control internal or surface defects individually, making it difficult to address both simultaneously. Therefore, they still have shortcomings in preparing high-quality perovskite thin films.

[0004] Therefore, there is an urgent need in this field to develop novel additives to prepare high-quality perovskite thin films. Summary of the Invention

[0005] To address the aforementioned problems in the prior art, this invention proposes a perovskite precursor solution, a perovskite light-absorbing layer, and a solar cell.

[0006] Specifically, the present invention provides a perovskite precursor solution, the perovskite precursor solution comprising a perovskite structural material raw material, a compound of formula I, and a solvent, wherein the compound of formula I has the following structure: ; In Formula I, R1 is selected from hydrogen atom, amino group, substituted or unsubstituted C1-C5 alkyl group, hydroxyl group, halogen atom, and carbonyl group; R2 is selected from hydrogen atom, amino group, substituted or unsubstituted C1-C5 alkoxy group, halogen atom, and mercapto group; R3 is selected from hydrogen atom, amino group, carbonyl group, substituted or unsubstituted C1-C5 alkoxy group, halogen atom, and hydroxyl group; R4 is selected from hydrogen atom, amino group, halogen atom, and substituted or unsubstituted C1-C5 alkyl group; and R5 is selected from hydrogen atom, amino group, halogen atom, and substituted or unsubstituted C1-C5 alkyl group.

[0007] In one or more embodiments, in Formula I, the substituents on the substituted C1-C5 alkyl group are selected from halogen atoms and amino groups.

[0008] In one or more embodiments, in Formula I, the substituents on the substituted C1-C5 alkoxy groups are selected from halogen atoms and amino groups.

[0009] In one or more embodiments, in Formula I, the halogen atom is selected from fluorine, chlorine, bromine and iodine atoms.

[0010] In one or more embodiments, in Formula I, R1 is selected from hydrogen atom, chlorine atom and amino atom, R2 is selected from amino atom, hydrogen atom, methoxy atom and bromine atom, R3 is selected from amino atom, hydrogen atom and methoxy atom, R4 is selected from amino atom and hydrogen atom, and R5 is selected from amino atom and hydrogen atom.

[0011] In some preferred embodiments, R1 is selected from hydrogen and chlorine atoms, R2 is selected from hydrogen, methoxy, and bromine atoms, R3 is selected from hydrogen and methoxy atoms, R4 is a hydrogen atom, and R5 is a hydrogen atom.

[0012] In one or more embodiments, the compound of formula I is selected from the following compounds: , , .

[0013] In one or more embodiments, the solvent is selected from one or more of N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, γ-butyrolactone, and acetonitrile.

[0014] In one or more embodiments, the concentration of the divalent cations in the perovskite structural material raw material in the perovskite precursor solution is 0.5-2 mol / L.

[0015] In one or more embodiments, the molar ratio of the compound of Formula I to the divalent cation in the perovskite structure material raw material is (0.005-1):100.

[0016] In some preferred embodiments, the molar ratio of the compound of formula I to the divalent cation in the perovskite structure material raw material is (0.01-0.5):100.

[0017] In some more preferred embodiments, the molar ratio of the compound of Formula I to the divalent cation in the perovskite structure material raw material is (0.01-0.1):100.

[0018] In another aspect, the present invention provides a perovskite light-absorbing layer, the perovskite light-absorbing layer comprising a perovskite structural material and a compound of formula I, the compound of formula I having the following structure: ; In Formula I, R1 is selected from hydrogen atom, amino group, substituted or unsubstituted C1-C5 alkyl group, hydroxyl group, halogen atom, and carbonyl group; R2 is selected from hydrogen atom, amino group, substituted or unsubstituted C1-C5 alkoxy group, halogen atom, and mercapto group; R3 is selected from hydrogen atom, amino group, carbonyl group, substituted or unsubstituted C1-C5 alkoxy group, halogen atom, and hydroxyl group; R4 is selected from hydrogen atom, amino group, halogen atom, and substituted or unsubstituted C1-C5 alkyl group; and R5 is selected from hydrogen atom, amino group, halogen atom, and substituted or unsubstituted C1-C5 alkyl group.

[0019] In one or more embodiments, in Formula I, the substituents on the substituted C1-C5 alkyl group are selected from halogen atoms and amino groups.

[0020] In one or more embodiments, in Formula I, the substituents on the substituted C1-C5 alkoxy groups are selected from halogen atoms and amino groups.

[0021] In one or more embodiments, in Formula I, the halogen atom is selected from fluorine, chlorine, bromine and iodine atoms.

[0022] In one or more embodiments, in Formula I, R1 is selected from hydrogen atom, chlorine atom and amino atom, R2 is selected from amino atom, hydrogen atom, methoxy atom and bromine atom, R3 is selected from amino atom, hydrogen atom and methoxy atom, R4 is selected from amino atom and hydrogen atom, and R5 is selected from amino atom and hydrogen atom.

[0023] In some preferred embodiments, R1 is selected from hydrogen and chlorine atoms, R2 is selected from hydrogen, methoxy, and bromine atoms, R3 is selected from hydrogen and methoxy atoms, R4 is a hydrogen atom, and R5 is a hydrogen atom.

[0024] In one or more embodiments, the compound of formula I is selected from the following compounds: , , .

[0025] In one or more embodiments, the molar ratio of the compound of Formula I to the divalent cation in the perovskite structure is (0.005-1):100.

[0026] In some preferred embodiments, the molar ratio of the compound of Formula I to the divalent cation in the perovskite structure is (0.01-0.5):100.

[0027] In some more preferred embodiments, the molar ratio of the compound of Formula I to the divalent cation in the perovskite structure is (0.01-0.1):100.

[0028] In one or more embodiments, the thickness of the perovskite light-absorbing layer is 800-1500 nm.

[0029] In another aspect, the present invention provides a method for preparing a perovskite light-absorbing layer as described in any one of the present invention, the method comprising coating a perovskite precursor solution according to any embodiment of the present invention, and then annealing to obtain a perovskite light-absorbing layer.

[0030] In one or more embodiments, the coating method is spin coating, blade coating, vapor deposition, printing, spraying, spray pyrolysis, or slot coating.

[0031] In one or more embodiments, the annealing temperature is 120-150°C.

[0032] In one or more embodiments, the annealing time is 10-30 minutes.

[0033] In another aspect, the present invention provides a solar cell comprising the perovskite light-absorbing layer described in any embodiment of the present invention.

[0034] Another aspect of the present invention provides the use of the compound of formula I in improving the short-circuit current density, open-circuit voltage, fill factor and / or conversion efficiency of solar cells containing perovskite light-absorbing layers, said compound of formula I having the following structure: ; In Formula I, R1 is selected from hydrogen atom, amino group, substituted or unsubstituted C1-C5 alkyl group, hydroxyl group, halogen atom, and carbonyl group; R2 is selected from hydrogen atom, amino group, substituted or unsubstituted C1-C5 alkoxy group, halogen atom, and mercapto group; R3 is selected from hydrogen atom, amino group, carbonyl group, substituted or unsubstituted C1-C5 alkoxy group, halogen atom, and hydroxyl group; R4 is selected from hydrogen atom, amino group, halogen atom, and substituted or unsubstituted C1-C5 alkyl group; and R5 is selected from hydrogen atom, amino group, halogen atom, and substituted or unsubstituted C1-C5 alkyl group.

[0035] In one or more embodiments, in Formula I, the substituents on the substituted C1-C5 alkyl group are selected from halogen atoms and amino groups.

[0036] In one or more embodiments, in Formula I, the substituents on the substituted C1-C5 alkoxy groups are selected from halogen atoms and amino groups.

[0037] In one or more embodiments, in Formula I, the halogen atom is selected from fluorine, chlorine, bromine and iodine atoms.

[0038] In one or more embodiments, in Formula I, R1 is selected from hydrogen atom, chlorine atom and amino atom, R2 is selected from amino atom, hydrogen atom, methoxy atom and bromine atom, R3 is selected from amino atom, hydrogen atom and methoxy atom, R4 is selected from amino atom and hydrogen atom, and R5 is selected from amino atom and hydrogen atom.

[0039] In some preferred embodiments, R1 is selected from hydrogen and chlorine atoms, R2 is selected from hydrogen, methoxy, and bromine atoms, R3 is selected from hydrogen and methoxy atoms, R4 is a hydrogen atom, and R5 is a hydrogen atom.

[0040] In one or more embodiments, the compound of formula I is selected from the following compounds: , , .

[0041] This invention optimizes the molecular structure of quinazolin-4-amine and its derivatives, enabling the designed molecules to react with divalent cations (such as Pb) in perovskites during crystallization. 2+ The formation of strong coordination helps control the crystallization of perovskite, and the functional groups of the designed molecules can also effectively passivate defects formed during the perovskite film formation process, thus significantly improving the quality of perovskite. Attached Figure Description

[0042] Figure 1 This is a schematic diagram of the perovskite solar cell structure in some embodiments of the present invention. Detailed Implementation

[0043] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used herein are explained and defined in general terms below. Unless otherwise specified, all technical and scientific terms used herein have the common meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.

[0044] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.

[0045] In this document, the terms “contains,” “includes,” “containing,” and similar terms encompass the meanings of “basically composed of” and “composed of.” For example, when this document discloses “A contains B and C,” “A is basically composed of B and C” and “A is composed of B and C” should be considered as having been disclosed in this document.

[0046] In this document, all features defined by numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values ​​(including integers and fractions) within those ranges.

[0047] Unless otherwise specified, percentages refer to mass percentages and proportions refer to mass ratios in this article.

[0048] In this article, the sum of the percentages of all components in the composition is 100%.

[0049] In this document, when describing embodiments or examples, it should be understood that it is not intended to limit the invention to those embodiments or examples. Rather, all alternatives, modifications, and equivalents of the methods and materials described herein are covered within the scope of this invention.

[0050] For the sake of brevity, not all possible combinations of the technical features in each implementation scheme or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation scheme or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.

[0051] In this invention, the number of Cs before a group indicates the number of carbon atoms contained in the group. For example, C1 alkyl represents an alkyl group containing one carbon atom, i.e., methyl, and C1 alkoxy represents an alkoxy group containing one carbon atom, i.e., methoxy.

[0052] In this invention, alkoxy refers to -O-alkyl.

[0053] In this invention, halogen atoms include fluorine, chlorine, bromine, and iodine.

[0054] In this invention, amino refers to -NH2.

[0055] In this invention, hydroxyl group refers to -OH.

[0056] In this invention, carbonyl refers to -C=O.

[0057] In this invention, the thiol group refers to -SH.

[0058] This invention provides a perovskite precursor solution, comprising a perovskite structural material raw material, a compound of formula I, and a solvent, wherein the compound of formula I has the following structure: ; In Formula I, R1 is selected from hydrogen atom, amino group, substituted or unsubstituted C1-C5 alkyl group, hydroxyl group, halogen atom, and carbonyl group; R2 is selected from hydrogen atom, amino group, substituted or unsubstituted C1-C5 alkoxy group, halogen atom, and mercapto group; R3 is selected from hydrogen atom, amino group, carbonyl group, substituted or unsubstituted C1-C5 alkoxy group, halogen atom, and hydroxyl group; R4 is selected from hydrogen atom, amino group, halogen atom, and substituted or unsubstituted C1-C5 alkyl group; and R5 is selected from hydrogen atom, amino group, halogen atom, and substituted or unsubstituted C1-C5 alkyl group.

[0059] In this invention, in the compound of formula I, the substituents on the substituted C1-C5 alkyl groups can be selected from halogen atoms and amino groups.

[0060] In this invention, in the compound of formula I, the substituents on the substituted C1-C5 alkoxy groups can be selected from halogen atoms and amino groups.

[0061] In this invention, the halogen atom in the compound of formula I can be selected from fluorine atom, chlorine atom, bromine atom and iodine atom.

[0062] In this invention, in the compound of formula I, R1 can be selected from amino, hydrogen atom and chlorine atom, R2 can be selected from amino, hydrogen atom and methoxy and bromine atom, R3 can be selected from amino, hydrogen atom and methoxy, R4 can be selected from amino and hydrogen atom, and R5 can be selected from amino and hydrogen atom.

[0063] In some preferred embodiments, R1 can be selected from hydrogen atoms and chlorine atoms, R2 can be selected from hydrogen atoms, methoxy groups and bromine atoms, R3 can be selected from hydrogen atoms and methoxy groups, R4 can be a hydrogen atom, and R5 can be a hydrogen atom.

[0064] In this invention, the compound of formula I may be selected from the following compounds: , , .

[0065] In this invention, the solvent may be selected from one or more of N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), N-methylpyrrolidone (NMP), γ-butyrolactone (GBL), and acetonitrile (AcN).

[0066] In this invention, the perovskite structure material raw material may include monovalent cations, divalent cations, and monovalent anions.

[0067] In this invention, the monovalent cation can be selected from one or more of formamidinium ion, cesium ion, methylamine ion, potassium ion and rubidium ion; the divalent cation can be selected from one or more of lead ion, copper ion, zinc ion, gallium ion, tin ion and calcium ion; and the monovalent anion can be selected from one or more of iodide ion, bromide ion, chloride ion, fluoride ion and thiocyanate ion.

[0068] In this invention, the concentration of divalent cations in the perovskite precursor solution can be 0.5-2 mol / L, for example 0.5 mol / L, 1 mol / L, 1.5 mol / L, or 2 mol / L.

[0069] In this invention, the molar ratio of the compound of Formula I to the divalent cation in the perovskite structural material raw material in the perovskite precursor solution can be (0.005-1):100, preferably (0.01-0.5):100, more preferably (0.01-0.1):100, for example 0.01:100, 0.02:100, 0.03:100, 0.04:100, 0.05:100, 0.06:100, 0.07:100, 0.08:100, 0.09:100, 0.1:100. Controlling the molar ratio of the compound of Formula I to the divalent cation within the above range can effectively passivate defects formed during the perovskite film formation process, thereby effectively improving the quality of the perovskite film.

[0070] The present invention also provides a perovskite light-absorbing layer comprising a perovskite structural material and a compound of formula I, as described above.

[0071] In this invention, the molar ratio of the compound of Formula I to the divalent cations in the perovskite structural material in the perovskite light-absorbing layer can be (0.005-1):100, preferably (0.01-0.5):100, more preferably (0.01-0.1):100, for example 0.01:100, 0.02:100, 0.03:100, 0.04:100, 0.05:100, 0.06:100, 0.07:100, 0.08:100, 0.09:100, 0.1:100. Controlling the molar ratio of the compound of Formula I to the divalent cations within the above range can effectively passivate defects formed during the perovskite film formation process, thereby effectively improving the quality of the perovskite film.

[0072] In this invention, the thickness of the perovskite light-absorbing layer can be 800-1500nm, for example 800nm, 900nm, 1000nm, 1100nm, 1200nm, 1300nm, 1400nm, and 1500nm.

[0073] In this invention, the band gap of the perovskite light-absorbing layer can be 1.3-2.3 eV, for example 1.3 eV, 1.4 eV, 1.5 eV, 1.6 eV, 1.7 eV, 1.8 eV, 1.9 eV, 2.0 eV, 2.1 eV, 2.2 eV, or 2.3 eV.

[0074] The present invention also provides a method for preparing the perovskite light-absorbing layer described above, the method comprising coating a perovskite precursor solution described above and then annealing to obtain the perovskite light-absorbing layer.

[0075] In the method of the present invention, the coating method can be spin coating, blade coating, vapor deposition, printing, spraying, spray pyrolysis, or slot coating.

[0076] In the method of this invention, the annealing temperature can be 120-150℃, for example 120℃, 125℃, 130℃, 135℃, 140℃, 145℃, or 150℃. The annealing time can be 10-30 min, for example 10 min, 12 min, 15 min, 20 min, 21 min, 25 min, or 30 min.

[0077] The present invention also provides a solar cell including the perovskite light-absorbing layer of the present invention.

[0078] In this invention, the solar cell can be a perovskite solar cell.

[0079] In this invention, the perovskite solar cell may sequentially include, in the thickness direction: a glass substrate, a transparent conductive oxide (TCO) layer, a hole transport layer, the perovskite light-absorbing layer of this invention, an electron transport layer, and a metal electrode layer.

[0080] In some implementations, a hole-blocking layer is also provided between the electron transport layer and the metal electrode layer.

[0081] In this invention, the transparent oxide can be one or more of the following: tin-doped indium oxide (ITO), fluorine-doped tin oxide (FTO), zinc-doped indium oxide (IZO), aluminum-doped zinc oxide (AZO), cerium-doped indium oxide (ICO), and zirconium-doped indium oxide (IZrO).

[0082] In this invention, the hole transport layer can be made of NiO. x It includes one or more of the following: doped compounds such as Li, Mg, and Cu, PTTA, PEDOT, or self-assembled single-molecule materials (SAMs).

[0083] Self-assembled monomolecular materials can be [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid, [2-(9H-carbazole-9-yl)ethyl]phosphonic acid, derivatives of [2-(9H-carbazole-9-yl)ethyl]phosphonic acid, [2-(9H-carbazole-9-yl)butyl]phosphonic acid, or derivatives of [2-(9H-carbazole-9-yl)butyl]phosphonic acid.

[0084] In this invention, the thickness of the hole transport layer can be 1-30nm, for example 1nm, 2nm, 5nm, 10nm, 15nm, 20nm, 25nm, or 30nm.

[0085] In this invention, the material of the electron transport layer can be one or more of [6,6]-phenyl-C61-butyrate methyl ester, C60, tin oxide, and LiF.

[0086] In this invention, the thickness of the electron transport layer can be 5-30nm, for example 5nm, 10nm, 15nm, 20nm, 25nm, or 30nm.

[0087] In this invention, the hole blocking layer can be made of one or more of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline, zirconium acetylacetonate, and SnO2.

[0088] In this invention, the thickness of the hole blocking layer can be 10-50nm, for example 10nm, 15nm, 20nm, 30nm, 40nm, or 50nm.

[0089] In this invention, the material of the metal electrode layer can be one or more of the following: silver, copper, tin-doped indium oxide (ITO), fluorine-doped tin oxide (FTO), zinc-doped indium oxide (IZO), aluminum-doped zinc oxide (AZO), cerium-doped indium oxide (ICO), zirconium-doped indium oxide (IZrO), and carbon electrode.

[0090] The present invention also provides the use of the compound of formula I in improving the short-circuit current density, open-circuit voltage, fill factor and / or conversion efficiency of solar cells containing perovskite light-absorbing layers, wherein the compound of formula I is as described herein.

[0091] The beneficial effects of this invention include: This invention incorporates quinazolin-4-amine and its derivatives as additives into the perovskite light-absorbing layer, effectively improving the perovskite surface morphology, making it smoother, promoting grain growth, and reducing grain boundary defects. Simultaneously, the additives can directly perform in-situ interface passivation at the interface between the perovskite and the electron transport layer, effectively reducing interface contact defects between the perovskite surface and the electron transport layer. This is because: (1) Amino (-NH2) can effectively passivate internal defects in perovskites; (2) Ring structures can form coordination with perovskite structural material raw materials (such as FA) to control perovskite crystallization; (3) The double-ring structure can remain at the grain boundary or surface without entering the perovskite lattice, thus passivating defects.

[0092] The present invention will be described below by way of specific embodiments. It should be understood that these embodiments are merely illustrative and are not intended to limit the scope of the invention. The methods, reagents, and materials used in the embodiments and comparative examples are conventional methods, reagents, and materials in the art, unless otherwise stated. The starting material compounds in the embodiments and comparative examples are all commercially available.

[0093] Example 1

[0094] This embodiment 1 provides an additive compound, quinazolin-4-amine, for use in perovskite solar cells, with the following structural formula: .

[0095] In Example 1, a perovskite solar cell was prepared according to the following steps: (1) TCO conductive glass (material is ITO) was ultrasonically cleaned with deionized water, acetone and isopropanol for 15 min in sequence, and then dried in a drying oven at 75℃ for later use. The dried TCO glass substrate was placed in an ultraviolet ozone machine for 25 min to remove organic impurities on its surface and optimize its surface wettability; (2) Dissolve 1 mg of [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid in 1 mL of isopropanol to prepare a hole transport material solution, and coat the hole transport material solution on a treated TCO glass substrate, and then anneal at 100 °C for 10 minutes to form a hole transport layer with a thickness of 5 nm. (3) Preparation of perovskite precursor solution: The perovskite structural materials (FAI, MAI, CsBr, PbI2, PbBr2), quinazolin-4-amine, and solvent (a mixed solution of DNF and DMSO, with a volume ratio of DNF to DMSO of 4:1) are mixed uniformly to form the perovskite precursor solution. In the perovskite precursor solution, Pb... 2+ The concentration was 1.7 mol / L, quinazoline-4-amine and Pb 2+ The molar ratio is 0.05:100; A perovskite precursor solution was coated onto the hole transport layer using a one-step spin-coating method, followed by annealing at 120℃ for 20 min. This yielded a quinazoline-4-amine-doped perovskite light-absorbing layer Cs with a band gap of approximately 1.68 eV and a thickness of 800 nm. 0.25 FA 0.75 Pb(I0.8 Br 0.2 3. In the perovskite light-absorbing layer, quinazoline-4-amine reacts with Pb 2+ The molar ratio is 0.05:100; (4) An electron transport layer with a thickness of 10 nm was prepared by thermal evaporation, using LiF and C60 as materials; (5) A hole blocking layer with a thickness of 15 nm was prepared by atomic layer deposition and the material was SnO2; (6) The back electrode was prepared by thermal evaporation with a thickness of 100 nm and the material was Ag metal grid wire.

[0096] Example 2

[0097] Example 2 provides an additive compound, 2-chloro-4-amino-6,7-dimethoxyquinazoline, for use in perovskite solar cells. Its structural formula is as follows: .

[0098] The steps for preparing perovskite solar cells in Example 2 are basically the same as those in Example 1, except that in step (3), quinazoline-4-amine is replaced with an equimolar amount of 2-chloro-4-amino-6,7-dimethoxyquinazoline in the perovskite precursor solution to prepare a 2-chloro-4-amino-6,7-dimethoxyquinazoline-doped perovskite light-absorbing layer Cs. 0.25 FA 0.75 Pb(I 0.8 Br 0.2 3. In the perovskite light-absorbing layer, 2-chloro-4-amino-6,7-dimethoxyquinazoline reacts with Pb 2+ The molar ratio is 0.05:100.

[0099] Example 3

[0100] This embodiment 3 provides an additive compound, 6-bromoquinazoline-4-amine, for use in perovskite solar cells, with the following structural formula: .

[0101] The steps for preparing perovskite solar cells in Example 3 are basically the same as those in Example 1, except that in step (3), quinazoline-4-amine is replaced with an equimolar amount of 6-bromoquinazoline-4-amine in the perovskite precursor solution to prepare a 6-bromoquinazoline-4-amine-doped perovskite light-absorbing layer Cs. 0.25 FA 0.75 Pb(I 0.8 Br 0.2 3. In the perovskite light-absorbing layer, 6-bromoquinazoline-4-amine reacts with Pb 2+ The molar ratio is 0.05:100.

[0102] Example 4

[0103] Example 4 provides an additive compound, quinazolin-4-amine, for use in perovskite solar cells, with the following structural formula: .

[0104] The steps for preparing perovskite solar cells in Example 4 are basically the same as those in Example 1, except that in step (3), quinazolin-4-amine and Pb are added to the perovskite precursor solution. 2+ A perovskite light-absorbing layer Cs doped with quinazoline-4-amine was prepared with a molar ratio of 0.5:100. 0.25 FA 0.75 Pb(I 0.8 Br 0.2 3. In the perovskite light-absorbing layer, quinazoline-4-amine reacts with Pb 2+ The molar ratio is 0.5:100.

[0105] Example 5

[0106] Example 5 provides an additive compound, quinazolin-4-amine, for use in perovskite solar cells. Its structural formula is shown below: .

[0107] The steps for preparing perovskite solar cells in Example 5 are basically the same as those in Example 1, except that in step (3), quinazolin-4-amine and Pb are added to the perovskite precursor solution. 2+ A perovskite light-absorbing layer Cs doped with quinazoline-4-amine was prepared by using a molar ratio of 1:100. 0.25 FA 0.75 Pb(I 0.8 Br 0.2 3. In the perovskite light-absorbing layer, quinazoline-4-amine reacts with Pb 2+ The molar ratio is 1:100.

[0108] Example 6

[0109] This embodiment 6 provides an additive compound, quinazolin-4-amine, for use in perovskite solar cells. Its structural formula is shown below: .

[0110] The steps for preparing perovskite solar cells in Example 6 are basically the same as those in Example 1, except that in step (3), quinazolin-4-amine and Pb are added to the perovskite precursor solution. 2+ With a molar ratio of 0.005:100, a quinazoline-4-amine-doped perovskite light-absorbing layer Cs was prepared.0.25 FA 0.75 Pb(I 0.8 Br 0.2 3. In the perovskite light-absorbing layer, quinazoline-4-amine reacts with Pb 2+ The molar ratio is 0.005:100.

[0111] Comparative Example 1

[0112] Comparative Example 1 prepared a perovskite solar cell according to the following steps: (1) TCO conductive glass (material is ITO) was ultrasonically cleaned with deionized water, acetone and isopropanol for 15 min in sequence, and then dried in a drying oven at 75℃ for later use. The dried TCO glass substrate was placed in an ultraviolet ozone machine for 25 min to remove organic impurities on its surface and optimize its surface wettability; (2) Dissolve 1 mg of [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid in 1 mL of isopropanol to prepare a hole transport material solution, and coat the hole transport material solution on the treated TCO glass substrate, and then anneal at 100 °C for 10 minutes to form a hole transport layer with a thickness of 5 nm. (3) Preparation of perovskite precursor solution: The perovskite structural material raw materials (FAI, MAI, CsBr, PbI2, PbBr2) and solvent (a mixed solution of DMF and DMSO, wherein the volume ratio of DMF to DMSO is 4:1) are mixed evenly to obtain a perovskite precursor solution. In the perovskite precursor solution, Pb 2+ The concentration was 1.7 mol / L; A perovskite precursor solution was coated onto the hole transport layer using a one-step spin-coating method, followed by annealing at 120℃ for 20 min, to prepare a perovskite light-absorbing layer Cs with a band gap of approximately 1.68 eV and a thickness of 800 nm. 0.25 FA 0.75 Pb(I 0.8 Br 0.2 3; (4) An electron transport layer with a thickness of 10 nm was prepared by thermal evaporation, using LiF and C60 as materials; (5) A hole transport layer with a thickness of 15 nm was prepared by atomic layer deposition and the material was SnO2; (6) The back electrode was prepared by thermal evaporation with a thickness of 100 nm and the material was Ag metal grid wire.

[0113] Comparative Example 2

[0114] Comparative Example 2 provides an additive compound, quinazoline, for use in perovskite solar cells, with the following structural formula: .

[0115] The steps for preparing the perovskite solar cell in Comparative Example 2 are basically the same as those in Example 1, except that in step (3), quinazoline-4-amine is replaced with an equimolar amount of quinazoline in the preparation of the perovskite precursor solution to obtain the quinazoline-doped perovskite light-absorbing layer Cs. 0.25 FA 0.75 Pb(I 0.8 Br 0.2 3. In the perovskite light-absorbing layer, quinazoline and Pb 2+ The molar ratio is 0.05:100.

[0116] Comparative Example 3

[0117] Comparative Example 3 provides an additive compound, phthalazine-1-amine, for use in perovskite solar cells, with the following structural formula: .

[0118] The steps for preparing the perovskite solar cell in Comparative Example 3 are basically the same as those in Example 1, except that in step (3), quinazoline-4-amine is replaced with an equimolar amount of phthalazine-1-amine in the preparation of the perovskite precursor solution to prepare the phthalazine-1-amine-doped perovskite light-absorbing layer Cs. 0.25 FA 0.75 Pb(I 0.8 Br 0.2 3. In the perovskite light-absorbing layer, phthalazine-1-amine reacts with Pb 2+ The molar ratio is 0.05:100.

[0119] Comparative Example 4

[0120] Comparative Example 4 provides an additive compound, 4-amino-pyridine, for use in perovskite solar cells, with the following structural formula: .

[0121] The steps for preparing the perovskite solar cell in Comparative Example 4 are basically the same as those in Example 1, except that in step (3), quinazoline-4-amine is replaced with an equimolar amount of 4-amino-pyridine in the preparation of the perovskite precursor solution to prepare the 4-amino-pyridine-doped perovskite light-absorbing layer Cs. 0.25 FA 0.75 Pb(I 0.8 Br 0.2 3. In the perovskite light-absorbing layer, 4-amino-pyridine and Pb 2+ The molar ratio is 0.05:100.

[0122] Comparative Example 5

[0123] Comparative Example 5 provides an additive compound, quinazolin-4-amine, for use in perovskite solar cells, with the following structural formula: .

[0124] The steps for preparing perovskite solar cells in Comparative Example 5 are basically the same as those in Example 1, except that in step (3), quinazolin-4-amine and Pb are added to the perovskite precursor solution. 2+ A perovskite light-absorbing layer Cs doped with quinazoline-4-amine was prepared with a molar ratio of 0.001:100. 0.25 FA 0.75 Pb(I 0.8 Br 0.2 3. In the perovskite light-absorbing layer, quinazoline-4-amine reacts with Pb 2+ The molar ratio is 0.001:100.

[0125] Comparative Example 6

[0126] Comparative Example 6 provides an additive compound, quinazolin-4-amine, for use in perovskite solar cells, with the following structural formula: .

[0127] The steps for preparing perovskite solar cells in Comparative Example 6 are basically the same as those in Example 1, except that in step (3), quinazolin-4-amine and Pb are added to the perovskite precursor solution. 2+ A perovskite light-absorbing layer Cs doped with quinazolin-4-amine was prepared by using a molar ratio of 5:100. 0.25 FA 0.75 Pb(I 0.8 Br 0.2 3. In the perovskite light-absorbing layer, quinazoline-4-amine reacts with Pb 2+ The molar ratio is 5:100.

[0128] Test case

[0129] Performance testing of perovskite solar devices: At 25 °C, a solar simulator (AM 1.5G standard solar spectrum, incident light power Pin 100 mW / cm²) was used. 2 The voltage range was set to -0.2 V to 1.5 V. The current output of the perovskite solar cells prepared in Examples 1-5 and Comparative Examples 1-6 was tested at different voltages, and the corresponding current-voltage (IV) characteristic curves were plotted. The effective area of ​​the cell was 1 cm². 2 The open-circuit voltage, short-circuit current density, fill factor, and photoelectric conversion efficiency of the perovskite solar cells prepared in Examples 1-5 and Comparative Examples 1-6 were obtained based on the characteristic curves.

[0130] (1) Open circuit voltage (Voc): The voltage value when the current is zero.

[0131] (2) Short-circuit current density (Jsc): When the voltage across the battery terminals is zero, the current density passing through a unit area of ​​the battery.

[0132] The magnitude of the current (Jsc).

[0133] (3) Fill factor (FF): The ratio of the battery’s maximum output power (Pmax) to the product of the open-circuit voltage and the short-circuit current. The formula is (Pmax / Voc×Isc)×100%, where the maximum power point is the point where the battery’s output power reaches its maximum value, and Isc is the short-circuit current.

[0134] (4) Photoelectric conversion efficiency (PCE): Photoelectric conversion efficiency refers to the ratio of maximum output power to incident light power (Pin), and the calculation formula is (Pmax / Pin)×100%.

[0135] The test results of open-circuit voltage, short-circuit current density, fill factor and photoelectric conversion efficiency of the perovskite solar cells prepared in Examples 1-6 and Comparative Examples 1-6 are shown in Table 1.

[0136] Table 1: Results of open-circuit voltage, short-circuit current density, fill factor, and photoelectric conversion efficiency of perovskite solar cells prepared in Examples 1-6 and Comparative Examples 1-6

[0137] As can be seen from the experimental results of Examples 1-3 and Comparative Example 1 in Table 1, the performance of solar cells prepared by using quinazoline-4-amine and its derivatives as additives to perovskite precursor solutions is better than that of solar cells prepared without additives.

[0138] As can be seen from the experimental results of Examples 1-3 and Comparative Examples 2-4 in Table 1, the performance of solar cells prepared by using quinazolin-4-amine and its derivatives as perovskite precursor solution additives is better than that of solar cells prepared by using non-NH2 compounds or monocyclic compounds as perovskite precursor solution additives.

[0139] As can be seen from the experimental results of Examples 1, 4-6 and Comparative Examples 5-6 in Table 1, quinazolin-4-amine and its derivatives react with Pb 2+ When the molar ratio is controlled within the range of (0.005-1):100, the prepared solar cells exhibit good performance. However, excessive additives not only affect the crystallization of the perovskite but also leave residues at the perovskite boundaries, hindering carrier transport and leading to a decrease in the fill factor.

Claims

1. A perovskite precursor solution, characterized in that, The perovskite precursor solution comprises a perovskite structural material raw material, a compound of formula I, and a solvent, wherein the compound of formula I has the structure shown below: ; In Formula I, R1 is selected from hydrogen atom, amino group, substituted or unsubstituted C1-C5 alkyl group, hydroxyl group, halogen atom, and carbonyl group; R2 is selected from hydrogen atom, amino group, substituted or unsubstituted C1-C5 alkoxy group, halogen atom, and mercapto group; R3 is selected from hydrogen atom, amino group, carbonyl group, substituted or unsubstituted C1-C5 alkoxy group, halogen atom, and hydroxyl group; R4 is selected from hydrogen atom, amino group, halogen atom, and substituted or unsubstituted C1-C5 alkyl group; and R5 is selected from hydrogen atom, amino group, halogen atom, and substituted or unsubstituted C1-C5 alkyl group.

2. The perovskite precursor solution as described in claim 1, characterized in that, In Formula I, the substituents on the substituted C1-C5 alkyl group are selected from halogen atoms and amino groups; In Formula I, the substituents on the substituted C1-C5 alkoxy groups are selected from halogen atoms and amino groups; In Formula I, the halogen atom is selected from fluorine, chlorine, bromine and iodine atoms; In Formula I, R1 is selected from hydrogen atom, chlorine atom and amino atom, R2 is selected from amino atom, hydrogen atom, methoxy atom and bromine atom, R3 is selected from amino atom, hydrogen atom and methoxy atom, R4 is selected from amino atom and hydrogen atom, and R5 is selected from amino atom and hydrogen atom.

3. The perovskite precursor solution as described in claim 1, characterized in that, In Formula I, R1 is selected from hydrogen and chlorine atoms, R2 is selected from hydrogen, methoxy, and bromine atoms, R3 is selected from hydrogen and methoxy atoms, R4 is a hydrogen atom, and R5 is a hydrogen atom.

4. The perovskite precursor solution as described in claim 1, characterized in that, The compound of formula I is selected from the following compounds: 、 、 。 5. The perovskite precursor solution as described in claim 1, characterized in that, The perovskite precursor solution has one or more of the following characteristics: The solvent is selected from one or more of N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, γ-butyrolactone, and acetonitrile; The concentration of divalent cations in the perovskite structural material raw material in the perovskite precursor solution is 0.5-2 mol / L; The molar ratio of the compound of Formula I to the divalent cation in the perovskite structure material raw material is (0.005-1):

100.

6. The perovskite precursor solution as described in claim 5, characterized in that, The molar ratio of the compound of Formula I to the divalent cation in the perovskite structure material raw material is (0.01-0.5):

100.

7. The perovskite precursor solution as described in claim 6, characterized in that, The molar ratio of the compound of Formula I to the divalent cation in the perovskite structure material raw material is (0.01-0.1):

100.

8. A perovskite light-absorbing layer, characterized in that, The perovskite light-absorbing layer comprises a perovskite structural material and a compound of formula I, wherein the compound of formula I has the following structure: ; In Formula I, R1 is selected from hydrogen atom, amino group, substituted or unsubstituted C1-C5 alkyl group, hydroxyl group, halogen atom, and carbonyl group; R2 is selected from hydrogen atom, amino group, substituted or unsubstituted C1-C5 alkoxy group, halogen atom, and mercapto group; R3 is selected from hydrogen atom, amino group, carbonyl group, substituted or unsubstituted C1-C5 alkoxy group, halogen atom, and hydroxyl group; R4 is selected from hydrogen atom, amino group, halogen atom, and substituted or unsubstituted C1-C5 alkyl group; and R5 is selected from hydrogen atom, amino group, halogen atom, and substituted or unsubstituted C1-C5 alkyl group.

9. The perovskite light-absorbing layer as described in claim 8, characterized in that, In Formula I, the substituents on the substituted C1-C5 alkyl group are selected from halogen atoms and amino groups; In Formula I, the substituents on the substituted C1-C5 alkoxy groups are selected from halogen atoms and amino groups; In Formula I, the halogen atom is selected from fluorine, chlorine, bromine and iodine atoms; In Formula I, R1 is selected from hydrogen atom, chlorine atom and amino atom, R2 is selected from amino atom, hydrogen atom, methoxy atom and bromine atom, R3 is selected from amino atom, hydrogen atom and methoxy atom, R4 is selected from amino atom and hydrogen atom, and R5 is selected from amino atom and hydrogen atom.

10. The perovskite light-absorbing layer as described in claim 8, characterized in that, In Formula I, R1 is selected from hydrogen and chlorine atoms, R2 is selected from hydrogen, methoxy, and bromine atoms, R3 is selected from hydrogen and methoxy atoms, R4 is a hydrogen atom, and R5 is a hydrogen atom.

11. The perovskite light-absorbing layer as described in claim 8, characterized in that, The compound of formula I is selected from the following compounds: 、 、 。 12. The perovskite light-absorbing layer as described in claim 8, characterized in that, The perovskite light-absorbing layer has one or more of the following characteristics: The molar ratio of the compound of Formula I to the divalent cation in the perovskite structure is (0.005-1):100; The thickness of the perovskite light-absorbing layer is 800-1500 nm.

13. The perovskite light-absorbing layer as described in claim 12, characterized in that, The molar ratio of the compound of Formula I to the divalent cation in the perovskite structure is (0.01-0.5):

100.

14. The perovskite light-absorbing layer as described in claim 13, characterized in that, The molar ratio of the compound of Formula I to the divalent cation in the perovskite structure is (0.01-0.1):

100.

15. A method for preparing a perovskite light-absorbing layer according to any one of claims 8-14, characterized in that, The method includes coating a perovskite precursor solution according to any one of claims 1-7, followed by annealing to obtain a perovskite light-absorbing layer.

16. The method as described in claim 15, characterized in that, The method has one or more of the following characteristics: The coating method is spin coating, blade coating, vapor deposition, printing, spraying, spray pyrolysis, or slot coating; The annealing temperature is 120-150℃; The annealing time is 10-30 minutes.

17. A solar cell, characterized in that, The solar cell includes the perovskite light-absorbing layer as described in any one of claims 8-14.

18. The use of the compound of Formula I in improving the short-circuit current density, open-circuit voltage, fill factor, and / or conversion efficiency of solar cells containing perovskite light-absorbing layers, characterized in that, The compound of formula I has the following structure: ; In Formula I, R1 is selected from hydrogen atom, amino group, substituted or unsubstituted C1-C5 alkyl group, hydroxyl group, halogen atom, and carbonyl group; R2 is selected from hydrogen atom, amino group, substituted or unsubstituted C1-C5 alkoxy group, halogen atom, and mercapto group; R3 is selected from hydrogen atom, amino group, carbonyl group, substituted or unsubstituted C1-C5 alkoxy group, halogen atom, and hydroxyl group; R4 is selected from hydrogen atom, amino group, halogen atom, and substituted or unsubstituted C1-C5 alkyl group; and R5 is selected from hydrogen atom, amino group, halogen atom, and substituted or unsubstituted C1-C5 alkyl group.

19. The use as described in claim 18, characterized in that, In Formula I, the substituents on the substituted C1-C5 alkyl group are selected from halogen atoms and amino groups; In Formula I, the substituents on the substituted C1-C5 alkoxy groups are selected from halogen atoms and amino groups; In Formula I, the halogen atom is selected from fluorine, chlorine, bromine and iodine atoms; In Formula I, R1 is selected from hydrogen atom, chlorine atom and amino atom, R2 is selected from amino atom, hydrogen atom, methoxy atom and bromine atom, R3 is selected from amino atom, hydrogen atom and methoxy atom, R4 is selected from amino atom and hydrogen atom, and R5 is selected from amino atom and hydrogen atom.

20. The use as described in claim 18, characterized in that, In Formula I, R1 is selected from hydrogen and chlorine atoms, R2 is selected from hydrogen, methoxy, and bromine atoms, R3 is selected from hydrogen and methoxy atoms, R4 is a hydrogen atom, and R5 is a hydrogen atom.

21. The use as described in claim 18, characterized in that, The compound of formula I is selected from the following compounds: 、 、 。